Applying a Linked-Course Model to Foster Inquiry & Integration in Large First Year Courses - Husband, Brian (Canadian Journal of Higher Education, 2015)
Many first-year university courses are large and content-driven, which can contribute to low student engagement and difficulty involving students in the dynamic, cross-disciplinary nature of inquiry. Learning communities can address these goals, but their implementation often poses logistical challenges, especially in large courses. Here, we apply learning communities using a linked-course model to enhance student engagement and inquiry across three large, first-year biology courses. These three courses (Discovering Biodiversity, Molecular and Cell Biology, and Biological Concepts of Health) offer different contexts for biological inquiry, introduce key biological concepts, and are connected through jointly mapped learning outcomes, shared online skill workshops, and integrative learning communities composed of students from each course. Diverse modes of student learning are used across the three courses, and contemporary problems are explored within classes and small group seminars, which promote the development of skills necessary for inquiry. This course structure requires the coordinated scheduling of seminars and interdisciplinary projects but allows flexibility in the use of lecture periods and online content while offering increased resource efficiency. Collectively, these courses provide opportunities for integration, skill development, and problem solving. In contrast to many other forms of learning communities, this particular model promotes both a disciplinary foundation and crossdisciplinary applications for large numbers of students.